General Principles of the Administrative Procedure. The Romanian Perspective - Emil BĂLAN; Dragoş Teodor TROANŢĂ REBELEŞ (Transylvanian Review of Administrative Sciences, 2007)
From our perspective, the administrative procedure represents in a simple way the rules that apply to the activities of public administration structures (even if it concerns the drafting, the execution or the control of administrative acts or the realization of administrative operations). In the context represented by the need for reform and modernization in the public sector, the administrative procedure has to systemize, simplify and unify public administration activity eliminating the contradictions between the administrative actions. The reform and modernization of public administration needs in our opinion to state and establish in a clear and prescriptive way the rules concerning the general administrative procedure, in other words – the rules that guide the decision making process, that assures openness and transparency, the respect of citizens’ rights and interests, the efficiency of public administration. Our paper – “General principles of public administration procedure. The Romanian perspective” analyzes some of the general principles that apply to the administrative procedure as they are formulated in the internal legal order, principles governing the administrative procedures that are not yet systemized and unified in the form of one complex law, representing the first stage of our project. Taking into consideration the internal experience, our future research in this project will continue this study, in order to realize the comparative dimension in two directions – one representing the level and experience of the European Union Member States and the other representing the European Union dimension.